Software educativo en ciencias naturales en séptimo grado de educación básica de la escuela Lcdo. Diego Minuche Garrido del cantón Machala 2014-2015. - Caiminagua Capa, Johanna Maricela (2015)
This research is based on the study on the acceptance and impact on the implementation of educational technology as the simulators, by reference to the PIPO educational software in the teaching-learning students in the seventh grade of elementary school education I lcdo. Minuche Diego Garrido, making them a significant learning.